Is volunteering for everyone? Volunteering opportunities for young ex-offenders. Issue 2 (11th April 2016) - Kirby, Amy
Abstract : Purpose: – The purpose of this paper is to explore volunteering opportunities for young adults with criminal records ("young ex-offenders"). Design/methodology/approach: – The study was conducted primarily in one London borough. It involved mapping volunteering opportunities for young ex-offenders and conducting in-depth interviews with young ex-offenders and practitioners from volunteer-involving organisations (VIOs) and resettlement organisations. Findings: – Several perceived benefits of volunteering for young ex-offenders were identified; particularly in relation to "softer" outcomes such as building confidence, learning new skills and developing a routine. Perceived challenges focused on whether or not organisations were able to provide volunteers with adequate levels of support; concerns about levels of engagement among volunteers and confusion over safeguarding procedures, particularly in relation to the obtaining of Disclosure and Barring Checks. Originality/value: – This paper offers practical insight into the scope of volunteering for young ex-offenders which may be of use to VIOs and resettlement organisations interested in providing such opportunities to young ex-offenders.